Analysis of Mediating Effect of Customer Perception in Relation to Service Quality and Customer’s Satisfaction in Online Banking Services (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Qualities of service act as significant in the competition, putting effect upon customer’s satisfaction. This research aims for assessing how service quality puts impact customers’ satisfaction in the online banking service.  E-SERVQUAL with dimensions: efficiency, fulfillment, security, quick responses and easiness to use has been utilized to assess services’ qualities of service rendered by bank over internet. The pilot’s study was done with 33 responses and cronbach’s alpha was 0.882, which shows that  the collected data is valid. A questionnaire comprising of 23 statements was made and 262 responses were analyzed by doing EFA through SPSSv21 and CFA & Structural Equation Modeling using SPPS AMOS 21.